Validitas Metode Polymerase Chain Reaction GeneXpert MTB/RIF pada Bahan Pemeriksaan Sputum untuk Mendiagnosis Multidrug Resistant Tuberculosis - Nurlina Sirait; Ida Parwati; Nina Susana Dewi; Nida Suraya (Majalah Kedokteran Bandung, 2013)
Control of tuberculosis is hampered by slow conventional diagnostic methods especially for the detection of multidrug resistant tuberculosis (MDR-TB). Early detection of MDR-TB is essential to interrupt MDR-TB transmission and reduce the death rate. The aim of this study was to assess the validity of polymerase chain reaction genexpert MTB/RIF examination, which is a rapid automated molecular examination for the detection of MDR-TB. The study was conducted at the Directly Observed Treatment Short-Course (DOTS) clinic at Dr. Hasan Sadikin General Hospital Bandung. Subjects were patients with suspected MDR-TB. The research sample was sputum which was subjected to microscopic examination, susceptibility test proportion methods in Lowenstein Jensen media and polymerase chain reaction genexpert MTB/RIF examination. During August 2012 until January 2013, 88 subjects were obtained, with most of them were 25–34 years old. There were 54 samples obtained that grew in culture and 34 samples did not grow while 3 samples were other Mycobacteria of tuberculosis. It was also found that 97.5% of rifampin-resistant samples were also resistant to isoniazid. Examination of GeneXpert MTB/RIF showed a sensitivity of 92.3%, specificity of 75% with an accuracy of 88.2%. In conclusion, GeneXpert MTB/RIF examination has high validity for diagnosing MDR-TB against M. tuberculosis gold standard resistance test using the proportion method in Lowenstein Jensen media. The examination is recommended for MDR-TB screening.